2012
DOI: 10.1103/physrevb.86.184110
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure phases of a hydrogen-rich compound: Tetramethylgermane

Abstract: The vibrational and structural properties of a hydrogen-rich Group IVa hydride, Ge(CH3)4, are studied by combining Raman spectroscopy and synchrotron X-ray diffraction measurements at room temperature and at pressures up to 30.2 GPa. Both techniques allow the obtaining of complementary information on the high-pressure behaviors and yield consistent phase transitions at 1.4 GPa for the liquid to solid and 3.0, 5.4, and 20.3 GPa for the solid to solid. The four high-pressure solid phases are identified to have t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…For example, the pressure-induced restricted rotation of NH 3 /CH 3 groups and the locked NH 3 /CH 3 positions in the compounds of dihydrogen bonding molecule of NH 3 BH 3 , CH 3 HgM, (M = Cl, Br, I) and (CH 3 ) 2 XM, (X = Sn or Tl) , can be reflected by the softening of NH 3 /CH 3 vibrational mode in the Raman spectra. This anomalous phenomenon could also be found in the high-pressure experiments of the hydrogen-rich compounds, X­(CH 3 ) 4 (X = Si, Ge, and Sn). ,, For the Si­(CH 3 ) 4 , this softening behavior existed with the pressure up to 9.0 GPa, while it is 1.4 and 0.9 GPa for Ge­(CH 3 ) 4 and Sn­(CH 3 ) 4 , respectively. Compared with these results, DMS is very easy to undergo phase transition via active rotation of the CH 3 groups to freezing in a position only at 3.6 GPa in view of such small molecule relatively.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…For example, the pressure-induced restricted rotation of NH 3 /CH 3 groups and the locked NH 3 /CH 3 positions in the compounds of dihydrogen bonding molecule of NH 3 BH 3 , CH 3 HgM, (M = Cl, Br, I) and (CH 3 ) 2 XM, (X = Sn or Tl) , can be reflected by the softening of NH 3 /CH 3 vibrational mode in the Raman spectra. This anomalous phenomenon could also be found in the high-pressure experiments of the hydrogen-rich compounds, X­(CH 3 ) 4 (X = Si, Ge, and Sn). ,, For the Si­(CH 3 ) 4 , this softening behavior existed with the pressure up to 9.0 GPa, while it is 1.4 and 0.9 GPa for Ge­(CH 3 ) 4 and Sn­(CH 3 ) 4 , respectively. Compared with these results, DMS is very easy to undergo phase transition via active rotation of the CH 3 groups to freezing in a position only at 3.6 GPa in view of such small molecule relatively.…”
Section: Resultsmentioning
confidence: 60%
“…From above we have found evidence for three phase transitions at approximately 1. nearly all the modes exhibit the blue-shift with increasing pressure, whereas the ν 6 and ν 7 modes show a softening behavior (the negative pressure coefficients of both modes are listed in Table 1), which is regarded as a typical characteristic of rotational motions of the CH 3 group. 33−35 This phenomenon has also been observed in pressure-induced investigation on X(CH 3 ) 4 (X = Si, Ge and Sn), 27,30,31 where equivalent CH 3 groups would not remain stable and rotate by certain angles due to pressure-induce increase of intra-and intermolecular interaction. Additionally, it is found that each mode has very different pressure coefficients, as shown in Table 1, and CH 3 stretch modes exhibit the most intensive pressure effects in liquid phase.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…However, the corresponding result shows inconsistency among the lattice parameters b/a, c/a, and angle β , which will happen if P2 1 /c symmetrical Ge(CH 3 ) 4 (TMGe) appears when compression almost possesses the same lattice parameters as TMS (Table 1). [52] Considering the application of external condition, nonhydrostatic situation of crystallized TMS could be a reasonable explanation for the abnormity, which leads to the lattice distortion compared with SnBr 4 , SiCl 4 , and SiBr 4 to undergo the structural change depending on temperature. [45,50,53] Whereas the SiH 4 under applied pressure is still kept as an excellent crystal with space group P2 1 /c as SnBr 4 , SiCl 4 , and SiBr 4 behave, suggesting that different pressure activities exist in both Si(CH 3 ) 4 compound and Ge(Ch 3 ) 4 compound.…”
Section: (B)mentioning
confidence: 99%